Predictive role of endometrial T-bet/GATA3 ratio during mid-luteal phase for live birth in patients undergoing in vitro fertilization: A retrospective observational study. (February 2022) - Li, Yuye; Yu, Shuyi; Huang, Chunyu; Diao, Lianghui; Chen, Cong; Liu, Wenjuan; Lian, Ruochun; Mo, Meilan; Du, Chenyang; Liu, Fenghua; Zeng, Yong
Highlights: Endometrial T-bet/GATA3 ratio was significantly higher in women with live birth than those patients with non-live birth. The endometrial T-bet/GATA3 ratio was an independent predictor of live birth. An endometrial T-bet/GATA3 ratio at the cut-off of 0.22 had significant predictive value for live birth. Abstract: Objectives: To investigate whether endometrial T-bet (Th1 lineage-committed transcription factor)/GATA3 (Th2 lineage-committed transcription factor) ratio has predictive potential for embryo implantation in infertile women undergoing in vitro fertilization-embryo transfer (IVF-ET). Study design: We performed a retrospective observational study. In total, this study included 319 infertile women (253 women as the development cohort and 66 women as the validation cohort). Samples were obtained by endometrial scratching in the mid-luteal phase before IVF-ET treatment. Main outcome measures: Immunohistochemistry was utilized to analyze the expression levels of T-bet and GATA3 in the endometrium. Predictive value of endometrial T-bet/GATA3 for live birth were analyzed. Results and conclusions: In the development cohort, the T-bet/GATA3 ratio was significantly lower in women with live birth than those patients with non-live birth [0.148 (0.101, 0.212) vs. 0.246 (0.170, 0.399), P ＜0.0001]. In the validation cohort, changes in endometrial T-bet/GATA3 were similar among these groups. The endometrial T-bet/GATA3 ratio was an independent predictor of live birth after correction for patient age, anti-Mullerian hormone (AMH), quality of embryos transferred and other clinical characteristics (aOR = 0.280, 95 % CI: 0.169–0.462, P ＜0.001). We developed and validated that an endometrial T-bet/GATA3 ratio at the cut-off of 0.22 had significant predictive value for live birth (developmental cohort: AUC = 0.76, 95 % CI: 0.70−0.81, P < 0.0001. validation cohort: AUC = 0.85 95 % CI: 0.76−0.95, P < 0.0001). Our results suggest that elevated endometrial T-bet/GATA3 ratio is an independent marker of live birth in infertile patients.